Medical-surgical nursing (Elsevier, 2016)
Using a unique collaborative care approach to adult health nursing, Medical-Surgical Nursing: Patient-Centered Collaborative Care, 8th Edition covers the essential knowledge you need to succeed at the RN level of practice. Easy-to-read content includes evidence-based treatment guidelines, an enhanced focus on QSEN competencies, and an emphasis on developing clinical judgment skills. This edition continues the book's trendsetting tradition with increased LGBTQ content and a new Care of Transgender Patients chapter. Written by nursing education experts Donna Ignatavicius and M. Linda Workman, this bestselling text also features NCLEXđ Exam-style challenge questions to prepare you for success on the NCLEX Exam. Cutting-edge coverage of the latest trends in nursing practice and nursing education prepares you not just for today's nursing practice but also for tomorrow's